An adult onset hexosaminidase A deficiency syndrome with sensory neuropathy and internuclear ophthalmoplegia. Issue 12 (December 1991) - Barnes, D; Misra, V P; Young, E P; Thomas, P K; Harding, A E
Abstract : A 42 year old man presented with a slowly progressive gait disturbance, generalised weakness, dysarthria, clumsiness and tremor of his hands, and involuntary jerks. Hexosaminidase A activity in plasma, leucocytes and fibroblasts was considerably reduced, establishing the diagnosis of GM2 gangliosidosis. Clinical examination showed two previously unreported features, a clinically evident sensory neuropathy and internuclear ophthalmoplegia.